SOME ASPECTS OF QUALITATIVE RESEARCH IN RESEARCHING LANGUAGE - Alpha Amirrachman (Indonesian JELT, 2006)
In the academic world, research inquiry is ‘bitterly’ divided into two competing paradigms: quantitative and qualitative research. Both are competing to search for revealing certain phenomenon and each of them claims to be the most satisfactory way to thoroughly discover the answer of the phenomenon. Firstly the article tries to illustrate the tension between the quantitative and qualitative research, the nature of qualitative research such as its epistemological positions, summary of the recurrent elements in qualitative research. Secondly, it explains qualitative research in language learning. The third part is on the methods in qualitative research such as case study, ethnography, observation and field interview. The fourth part is on ethical issues. Fifthly, the article discusses reliability and validity. The sixth part is on sampling. The seventh part is on the dynamic nature of research questions and the role of theory. The eighth part is on qualitative data analysis. The ninth part is on teacher-researcher and action research. The tenth part is on the structure of qualitative research proposal and the last part is on the introduction of qualitative research in Indonesia. It is perceived that there are various aspects in language learning that can be explored with the use of qualitative research, ranging from foreign language acquisition and language teaching policy. Keywords:  quantitative and qualitative research, epistemological positions, case study, ethnography, observation, field interview.